Optimal management of digital ulcers in systemic sclerosis - Abraham S; Steen V (Dove Medical Press, 2015)
Shawn Abraham, Virginia SteenDivision of Rheumatology, Immunology, and Allergy, MedStar Georgetown University Hospital, Washington, DC, USAAbstract: Raynaud’s phenomenon and digital ulcerations are two common clinical features seen in patients with systemic sclerosis. They are painful and lead to significant morbidity and altered hand function within this patient population. While currently there are no US Food and Drug Administration (FDA)-approved medications for the treatment of digital ulcerations in the United States, clinical trials have supported the use of pharmacologic and nonpharmacologic modalities in facilitating healing of existing digital ulcers and preventing formation of new ulcers. This article reviews the published data on these therapeutic options.Keywords: scleroderma, systemic sclerosis, Raynaud’s phenomenon, digital ulcers, treatment